2020
DOI: 10.1002/jac5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asymptomatic pyuria in psychiatric patients discharged from the emergency department following antimicrobial stewardship implementation

Abstract: Introduction Abnormal urinalysis (UA) results, such as pyuria or bacteriuria, increase the risk for antibiotic treatment even in the absence of urinary symptoms. In the emergency department (ED), patients presenting with psychiatric emergencies commonly undergo a medical assessment which includes a UA. We hypothesized that the rate of inappropriate antibiotic treatment for asymptomatic pyuria in the psychiatric medical population would decrease following implementation of an antimicrobial stewardship program (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Effectiveness of interventions was similar across study sizes (smaller24 153–156 vs larger106 135 138 157 158), locations (single-site73 159–162 vs multisite85 124 163–165), quality (lower72 74 75 83 166 vs higher127 128 139–141) and designs (uncontrolled79 104 105 107 133 vs controlled86 125 126 167 168). Multifaceted interventions were more likely to be effective than single-faceted interventions.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Effectiveness of interventions was similar across study sizes (smaller24 153–156 vs larger106 135 138 157 158), locations (single-site73 159–162 vs multisite85 124 163–165), quality (lower72 74 75 83 166 vs higher127 128 139–141) and designs (uncontrolled79 104 105 107 133 vs controlled86 125 126 167 168). Multifaceted interventions were more likely to be effective than single-faceted interventions.…”
Section: Discussionmentioning
confidence: 83%
“…Education,73–77 audit and feedback,78–82 stakeholder engagement,24 83–86 clinical decision support,87–91 nudge,92–96 clinical champions,97–101 training102–106 and incentives79 107 were the component facets of interventions. Interventions were multifaceted in 79% (113/143) of studies and single faceted in 21% (30/143) of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study evaluating ASB treatment in ED psychiatric patients before and after establishing an ID pharmacist-led culture review also found no difference in 72-h ED revisit, despite significantly decreased ASB treatment rates after program initiation. 15 This study is not without limitations, including that it is a retrospective analysis, potentially resulting in incomplete data collection and confounders. Limited documentation describing UTI symptoms potentially identified during patient outreach by the UCRP team could also factor into whether treatment is truly appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of ASB‐treated patients in the before pharmacist integration arm who, by definition, have no active infection, have a lower likelihood of ED revisit and may play a role in why no difference was seen. A recent study evaluating ASB treatment in ED psychiatric patients before and after establishing an ID pharmacist‐led culture review also found no difference in 72‐h ED revisit, despite significantly decreased ASB treatment rates after program initiation 15 …”
Section: Discussionmentioning
confidence: 99%